METHODS OF QUICK AND QUALITY DRYING OF FRUIT AND VEGETABLE PRODUCTS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In our country, great attention is paid to the drying of fruits and vegetables, and as a result, small-sized mini-drying shops are developing rapidly and intensive drying processes are being improved without wasting fruit quickly. Scientists of the Namangan Institute of Engineering and Technology are conducting research on the rapid and high-quality drying of fruits and vegetables. This article provides analytical data for the selection of specific production conditions for fruit and vegetable drying methods.